DERIVATIONAL SUFFIXES FORMING NOUN FROM VERB FOUND IN REVENGE WEARS PRADA NOVEL: A MORPHOLOGICAL STUDY - Rahmawati, Ni Kadek Liana; Sulatra, I Komang; Putra, I G. B. Wahyu Nugraha (Journal of Language and Applied Linguistics, 2021)
This study focuses on derivation from verb forming noun found in Revenge Wears Prada novel written by Lauren Weisberger. The aim of this study is to find out kind of suffixes used in forming noun from verb by applying the theory of nominal suffixes proposed by Plag (2003). The data were taken from novel entitled Revenge Wears Prada which was written by Lauren Weisberger. Observation method was used in collecting the data with several steps applied such as reading, note taking, and classifying technique continue with the theory of nominal suffixes proposed by Plag. There were 236 data using suffixes which form noun from verb, those data using suffixes -age, -al, -ance, -ant, -ee, -er/-or, -ing, -ion, and -ment. Moreover, several suffixes used repeatedly in the same word in this novel to form noun class category from different word class and all of these data categorized as class changing process since these morphological processes of verb forming noun has changed the class category of the base form. This study shows that morphology is very important in language since the used of morphological process helps to develop new word from several languages and word classes.